Effects of a highly concentrated platelet-rich plasma on the bone repair using non-critical defects in the calvaria of rabbits - Oliveira Filho,Marco Antonio de (2010)
PURPOSE: To verify the effect of highly concentrated platelet-rich plasma (hPRP) in the pathways of bone repair using non-critical defects in the calvaria of rabbits. METHODS: The hPRP was produced from collected venous blood of 21 rabbits. Four non-critical defects of 8 mm in diameter were created on the calvaria of each animal. The defects were all treated differently: autogenous particled bone (APB, group 1), autogenous particled bone associated with hPRP (APB + hPRP, group 2), isolated hPRP (group 3), and blood clot (control, group 4). Animals were submitted to euthanasia on the 2nd, 4th and 6th week postoperatively. Histological and histomorphometric analysis were carried through. RESULTS: After two weeks, groups 1 and 2 were in more advanced stage of repair than 3 and 4. At this period, comparing the groups 1 and 2, no significant differences were found between both, which also happened between the groups 3 and 4. However, after four and six weeks, the group 1 showed a more advanced stage of repair among all the other studied groups, while group 2 was in more advanced signs of bone repair than groups 3 and 4. Comparing groups 3 and 4, after four and six weeks, the least advanced stage of bone repair was found to be within group 3. CONCLUSION: The use of a highly concentrated PRP was considered prejudicial to the repair of non-critical defects in the calvaria of rabbits, either in the association of autogenous particled bone, when compared to autogenous particled bone alone, or in its isolated form, when compared to blood clot (control).